FORMING PRACTICAL ACTIVITY OF PRIMARY CLASS STUDENTS. - Umarova, Gozalkhon; Koshakova, Obidakhan (University Research Base, 2024)
The most important feature of the elementary mathematics course is its practical orientation. If some issues of the mathematics program in higher grades are theoretical in nature, in elementary school every new concept, property, law is introduced as a result of practical activity and for practical activity. For example, in the VII grade, students master the concept of a rectangle, they know the definition of a rectangle, logically derive its symptoms and prove some of its properties, logically derive its symptoms means that they know how to logically derive its symptoms and prove some properties, logically derive its symptoms and use them to solve practical problems related to some of its properties. In the elementary grades, students determine the equality of the opposite sides of a rectangle by measuring, and learn to construct a rectangle, measure its perimeter and face, and calculate. they learn Most of the practical learning that students develop in elementary school is of primary importance for the school mathematics course. Arithmetic operations in writing and speaking, formed in lower grades, are used in middle grades as well as in upper grades. One of the main tasks of a primary school teacher is to form thorough practical learning and skills in students. In this, it is necessary to solve two methodological problems that are interconnected.